Stem borer and leafhopper‐planthopper resistance in rice varieties - Pathak, M.D. (Wiley, 1969)
A total of 10,000 varieties, representing the world rice germ plasm collection at the International Rice Research Institute, were evaluated for their resistance to the striped borer, Chilo suppressalis Walker, in field and greenhouse experiments. From these, 20 varieties were recorded as highly resistant. The resistance appears to be non‐preference and/or antibiosis in nature. Several plant morphological and anatomical characters have been recorded to be correlated with stem borer resistance. On resistant varieties, the borer larvae suffer high mortality, have a slower rate of growth, and their body‐size is smaller than those of the larvae reared on susceptible hosts.The selected resistant varieties have been also used in a hybridization program which sought to combine stem borer resistance with improved plant type and other desirable characters. Several progenies of one such cross between TKM‐6 (resistant to borers) and Peta3 × Taichung (Native) 1 (improved plant type) are particularly promising. They are of improved plant type, resistant to borers, tolerant to the green leafhopper, Nephotettix impicticeps and the brown planthopper, Nilaparvata lugens, and possess some resistance to the tungro virus, bacterial leaf blight, bacterial leaf streak and the local races of the blast disease. They have high yield potentials and fine‐quality grains.The screening of about 1,000 rice varieties led to the identification of some varieties with natural resistance to the brown planthopper and to the rice green leafhopper. Resistance to the brown planthopper appears to be due to the presence of a strong repellent or a lack of feeding stimulus in the plants, while resistance to the green leafhopper is due either to the presence of toxic materials or nutritional deficiencies in the plant for the insect.ZUSAMMENFASSUNGSTENGELBOHRER‐ UND ZIKADEN‐RESISTENZ BEI REISSORTENEine Gesamtheit von 10,000 Varietäten, die beim Internationalen Reis‐Forschungs‐Institut das Welt‐Reis‐Sortiment darstellen, wurde auf ihre Resistenz gegenüber dem Gestreiften Stengelbohrer, Chilo suppressalis, in Feld‐ und Gewächshausversuchen geprüft. Unter diesen werden 20 als hochresistent bewertet. Die Resistenz scheint Nonpräferenz‐ und/oder Anti‐biosis‐Charakter zu haben. Verschiedene morphologische und anatomische Eigenschaften der Pflanzen sollen in Beziehung zur Stengelbohrer‐Resistenz stehen. Auf resistenten Pflanzen erleiden die Stengelbohrer‐Larven hohe Mortalität, haben eine geringere Wachstumsrate, und ihre Körpergröße ist geringer als die von Larven, welche auf anfälligen Wirten aufgezogen wurden.Die selektierten resistenten Varietäten sind auch in einem Hybridisierungs‐Programm benutzt worden, das die Stengelbohrer‐Resistenz mit einem verbesserten Pflanzentyp und anderen wünschenswerten Eigenschaften zu verbinden sucht. Verschiedene Nachkommenschaften einer solchen Kreuzung zwischen TKM‐6 (resistent gegen Stengelbohrer) und Peta3 × Taichung (wild) 1 (verbesserter Pflanzentyp) sind besonders vielversprechend. Sie haben einen verbesserten Pflanzentyp, sind widerstandsfähig gegen Stengelbohrer, tolerant gegen die Grüne Zwergzikade, Nephotettix cincticeps und die Braune Spornzikade, Nilaparvata lugens, und besitzen eine gewisse Resistenz gegen das Tungro‐Virus, bakteriellen Blattmehltau, bakterielle Blattstreifen und lokale Rassen der Pestkrankheit. Sie haben hohe Ertragspotentiale und gute Kornqualität.Die Prüfung von etwa 1000 Reissorten führte zur Feststellung einiger Varietäten mit natürlicher Resistenz gegen die Braune Spornzikade und die Grüne Zwergzikade. Die Resistenz gegen die Braune Spornzikade scheint auf der Anwesenheit eines starken Repellents oder auf dem Fehlen eines Fraßstimulants in den Pflanzen zu beruhen, während die Resistenz gegen die Grüne Zwergzikade entweder eine Folge der Anwesenheit toxischer Stoffe oder minderer Nahrungsqualität der Pflanze für das Insekt ist.